Identifying Factors Driving the Adoption of Halal Meat Products by Generation Z in Indonesia - Fasha, Andina; Yang, Wendy Wiranata; Ramadani, Arienda Gitty; Yuwono, Wisnu (Forum Kerjasama Pendidikan Tinggi, 2026)
This study investigates the factors influencing the intention of Generation Z consumers in Indonesia the world’s most populous Muslim nation to purchase halal meat products. Utilizing a quantitative approach, the research evaluates four key variables: Halal Supply Chain Knowledge, Halal Certification and Logo, Religious Belief, and Halal Awareness. Data were collected via an online survey of 300 Generation Z respondents. The analysis reveals that Religious Belief exerts the strongest significant influence on purchase intention, followed by Halal Awareness. Conversely, Halal Supply Chain Knowledge and Halal Certification/Logo demonstrated a negligible impact on purchase intent within this demographic. These findings suggest that for Generation Z, internal value systems and environmental consciousness outweigh formal logistics or labeling. The study recommends that the Indonesian government and private sector enhance education and certification transparency to bridge the gap between formal standards and consumer trust, thereby increasing the global competitiveness of the Indonesian halal industry.